The potential application of carbazole-degrading bacteria for dioxin bioremediation - Mai Thi Ngoc Dinh; Van Thi Nguyen; Ly Thi Huong Nguyen (Bioresources and Bioprocessing, 2023)
Abstract Extensive research has been conducted over the years on the bacterial degradation of dioxins and their related compounds including carbazole, because these chemicals are highly toxic and has been widely distributed in the environment. There is a pressing need to explore and develop more bacterial strains with unique catabolic features to effectively remediate dioxin-polluted sites. Carbazole has a chemical structure similar to dioxins, and the degradation pathways of these two chemicals are highly homologous. Some carbazole-degrading bacterial strains have been demonstrated to have the ability to degrade dioxins, such as Pseudomonas sp. strain CA10 và Sphingomonas sp. KA1. The introduction of strain KA1 into dioxin-contaminated model soil resulted in the degradation of 96% and 70% of 2-chlorodibenzo-p-dioxin (2-CDD) and 2,3-dichlorodibenzo-p-dioxin (2,3-DCDD), respectively, after 7-day incubation period. These degradation rates were similar to those achieved with strain CA10, which removed 96% of 2-CDD and 80% of 2,3-DCDD from the same model soil. Therefore, carbazole-degrading bacteria hold significant promise as potential candidates for dioxin bioremediation. This paper overviews the connection between the bacterial degradation of dioxins and carbazole, highlighting the potential for dioxin biodegradation by carbazole-degrading bacterial strains.